Pengembangan Media PAPIN (Papan Pintar) Kegimi (Kegiatan Ekonomi) Pada Mata Pelajaran IPS Kelas 4 SD Negeri 142 Palembang - Anissa syalsadilla; Kiki Aryaningrum M.Pd; Hetilaniar, M.Pd (Jurnal Pendidikan Sosial Dan Konseling, 2024)
Based on the problems at SD Negeri 142 Palembang, the lack of use of media in social studies learning makes it difficult for students to understand the material on theme 8 "The Area Where I Live" sub-theme 2 learning to 4. This research aims to produce learning media Papin Kegimi (Smart board for economic activities) which is suitable ;id, practical, and potential effects. The type of research method used is Research and Development (R&D) with the ADDIE Model. Based on the analysis of student learning outcomes, it is known that out of 20 students, only 5 students have not achieved the KKM score, while 17 students already understand the material in My Area of ​​Residence. The development of the Papin Kegimi Media (Smart Board for Economic Activities) in the fourth grade social studies subject at SD Negeri 142 Palembang has produced a learning media product that has been declared valid by media, material and language experts. The results of the Papin Kegimi media research were declared valid with an average result of 86.91% in the "very valid" category of student response questionnaires with results of 94.41% in the "very practical" category. The test results obtained from students had an average of 85.23% in the "very effective" category. So it can be concluded that in the research on the development of Papin Kegimi media for the fourth grade social studies subjects at SD Negeri 142 Palembang, there is validity, practicality and effectiveness. Keywords: Media, Papin Kegimi, Social Sciences.